SURVEILLANCE ANALYSIS OF CLEAN AND HEALTHY LIVING BEHAVIOR (CHLB) IN HOUSEHOLD SETTINGS: A CASE STUDY IN LAM GEU EU VILLAGE, PEUKAN BADA SUBDISTRICT, ACEH BESAR REGENCY - Lensoni; Idroes, Ghazi Mour; Riski, Fhonna; Safira, Meylia; Ulfa, Natasya; Wahyu, Reski; Yani, Suci Madan (Transpublika Publisher, 2022)
Promoting clean and healthy living within households is essential for community well-being. This study employed a quantitative descriptive approach to conduct Public Health and Behavioral Surveillance (PHBS) in Lam Geu Eu Village. The objective of this study is to gather comprehensive data regarding the adoption of clean and healthy lifestyles among Lam Geu Eu Village residents. The study encompasses the entire population of Lam Geu Eu Village, located in the Peukan Bada Subdistrict of the Aceh Besar District, with a total of 473 Family Cards. Among these, a sample of 220 families was selected. The research occurred over a month, from June 22 to July 24, 2023. Results indicate that many clean and healthy living indicators have reached or nearly reached target goals. Key indicators include clean water use, assisted deliveries, and fruit/vegetable consumption. Areas for improvement include eradicating mosquito larvae, increasing physical activity, and promoting handwashing. This study underscores the importance of clean and healthy behaviors in enhancing community well-being and represents a positive step towards improving overall population health.